Verificação ao cisalhamento em alvenaria estrutural – estudo comparativo entre a atual ABNT NBR 16868 e proposta de atualização - Sanchez, Liz Andrea Cuevas (Universidade Federal de São Carlos, 2025)
The present work demonstrates a critical and analytical evaluation of the shear verification in structural masonry through the comparison between ABNT NBR 16868-1:2020, Eurocode 6 EN 1996-1-1:2005 and two proposals for normative update. The research used a set of 144 real walls extracted from three buildings (Building A = 45; Building B = 56; Building C = 43) to compare the different formulations and observe how variables, such as grouting area, effective area, normal pre-compression stress and presence of vertical reinforcement, alter the shear strength prediction. The results showed that the formulation of ABNT NBR 16868 tends, in many cases, to overestimate the resistant capacity when considering the gross area without explicitly discounting the mortar, while the Eurocode generally indicates more conservative values, on the other hand the proposals for updating studied start to discriminate grouted and non-grouted sections, to incorporate the net mortar area and the contribution of vertical reinforcement, producing predictions more consistent with the expected mechanical behavior. In practical terms, the study shows that the sensitivity to the degree of grouting and pre-compression is expressive, which can explain the discrepancies between methods, thus, walls with a low degree of grouting show greater percentage differences between standards, and buildings with high or varied levels of pre-compression tend to amplify these differences. An illustrative example of the study reveals relevant numerical discrepancies, where the shear strength values according to ABNT NBR 16868, Eurocode and the proposals presented were 211.03 kN; 164.51 kN; 196.96 kN and 198.56 kN, respectively, showing how normative hypothesis choices directly impact design checks and decisions. inally, the work emphasizes that, although the proposals correct observed distortions, their normative adoption would require additional experimental validation and clear on-site inspection procedures to ensure practical applicability.
Shear verification in structural masonry – comparative study between the current ABNT NBR 16868 and the proposed update
Keywords: Alvenaria Estrutural; Cisalhamento; Norma Técnica; Sistemas Construtivos; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; 9. Indústria, Inovação e Infraestrutura